2018
DOI: 10.1093/ageing/afy018
|View full text |Cite
|
Sign up to set email alerts
|

Pain assessment in the older population: what the literature says

Abstract: Assessment of pain in the older adult presents a number of challenges, especially related to communication. This commentary summarises the revised evidence-based Guidelines on the Assessment of Pain in Older Adults which have been developed by the British Pain Society and British Geriatrics Society. The guideline summarises the pain assessment tools that have been developed and validated for use in the older population. Recommendations are made for use of specific tools in older people and in those with dement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 14 publications
0
36
0
1
Order By: Relevance
“…Chronic pain associated with musculoskeletal disorders among institutionalized older adults (i.e., those living in assisted living and nursing home settings) is a critically important symptom to consider and address given the negative impact it has on the individuals' mood, activity, behavior, and overall life satisfaction (Bauer et al, 2016;Corbett et al, 2016;Karadag Arli, Bakan, Varol, & Aslan, 2018;Klapwijk, Caljouw, Pieper, van der Steen, & Achterberg, 2016). The percentage of individuals in institutional settings with pain ranged from 25 to 90% depending on the population studied and measures used (Brown, Kirkpatri, Swanson, & McKenzie, 2011;Schofield & Abdulla, 2018). It has been repeatedly noted that pain was under-reported, underrecognized, and under-treated among older adults in long term care settings (Fain, et al, 2017;Ferrell, Ferrell, & Revera, 1995;Hendriks, Smalbrugge, Galindo-Garre, Hertogh, & Van der Steen, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic pain associated with musculoskeletal disorders among institutionalized older adults (i.e., those living in assisted living and nursing home settings) is a critically important symptom to consider and address given the negative impact it has on the individuals' mood, activity, behavior, and overall life satisfaction (Bauer et al, 2016;Corbett et al, 2016;Karadag Arli, Bakan, Varol, & Aslan, 2018;Klapwijk, Caljouw, Pieper, van der Steen, & Achterberg, 2016). The percentage of individuals in institutional settings with pain ranged from 25 to 90% depending on the population studied and measures used (Brown, Kirkpatri, Swanson, & McKenzie, 2011;Schofield & Abdulla, 2018). It has been repeatedly noted that pain was under-reported, underrecognized, and under-treated among older adults in long term care settings (Fain, et al, 2017;Ferrell, Ferrell, & Revera, 1995;Hendriks, Smalbrugge, Galindo-Garre, Hertogh, & Van der Steen, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Provider and caregiver factors include: (1) an assumption that pain is a normal part of aging; (2) lack of knowledge for how to evaluate pain in older adults; (3) difficulties in provider-staff communication; and (4) the possibility that staff may become desensitized to pain (Herr, 2011;Herr et al, 1998;Herr & Mobily, 1991;1993;Herr et al, 2004;Ngu et al, 2015;Schofield, 2006;Veal et al, 2018). Measurement issues include the lack of consistency between objective and subjective measures of pain among older adults, particularly among those with cognitive impairment (Schofield & Abdulla, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This is concerning given that poor pain assessment has been cited as an important barrier to adequate pain control. 35 Research shows that pain is an important symptom in around a third of the older population, 4 35 36 ; it is therefore crucial that frequent comprehensive pain assessment is provided. 37 We found that in all countries more than half of GPs did not communicate with the patient (except for those aged 65-84 years in Belgium) regarding illness-related topics and were not aware of their preferences about medical treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Among persons with cognitive disorders, however, assessment of pain can be challenging [5]. Self-report is important in mild-tomoderate AD, but observational pain scales, such as Pain Assessment in Advanced Dementia (PAINAD) and Pain Assessment Checklist for Seniors with Limited Ability to Communicate (PACSLAC) [39,40], become more useful as the disease progresses [5,41,42]. Frequent use of opioids months after the hip fracture among persons with AD in this study may indicate the challenges of pain assessment.…”
Section: Discussionmentioning
confidence: 99%